Emissão de gases de efeito estufa, ciclagem de nutrientes e produtvidade de arroz irrigado em função de manejos póscolheita e plantas de cobertura - Grohs, Mara (2018)
The flooded rice production goes through a period of stagnation of productivity and low profitability in the state of Rio Grande do Sul. One of the factors contributing to this scenario is the low fertility of lowland soils, in part as a consequence of the intense upwelling of the soil causing high investments in fertilization. The adoption of a no-tillage system associated with the use of winter cover crops could contribute to the diversification of lowland land use, improved soil fertility and reduced activity costs combined with environmental sustainability. In this sense, with the objective of studying the influence of cover crops and post-harvest management of rice straw on nutrient cycling, flooded rice yield and greenhouse gas emissions, experiments were conducted during the 2015/16 and 2016/17 in the didacticexperimental lowland area of the Universidade Federal de Santa Maria. The first experiment was conducted to evaluate the influence of ryegrass, oats, seradella and wheat on nutrient cycling, rice yield and greenhouse gas emissions. In the second experiment, different postharvest management in the rice straw, represented by the use of grate, roller with flooded soil, straw roll in dry soil and dried straw were evaluated, associated or not with the use of ryegrass. In this work, the yield of flooded rice and the emission of greenhouse gases, methane and nitrous oxide, as well as the partial global warming potential and the yield of grains were evaluated. The use of cover plants makes it difficult to establish the initial rice, reducing the grain yield, in the order of 18%, in the average of two years. The decomposition and release of the nutrients from the straw of the cover plants are linked to the C/N ratio and the climatic conditions of the post-desiccation period. Ryegrass and oats increase the emission of methane and nitrous oxide during the flooded rice crop. No-tillage systems do not affect flooded rice productivity when compared to traditional systems and serve as a strategy to reduce partial global warming potential in areas with ryegrass.